Radiation Dose of Abdominal and Lung Computed Tomography Based on Body Mass Index as an Indicator - Sulayman, Muhammad Kabeer; Umar, Farouk Kabir; Lukuman, Bashiru; Karim, Muhammad Khalis Abdul; Muhammad, Nor Azura; Kamal, Izdihar; Che Abdullah, Che Azura; Mohd Radzi, Juliana; Ahmad Kamarudin, Mazliana (Malaysian Journal of Medical Sciences, 2025)
Background: Radiation dose generated from computed tomography (CT) has drawn more attention to diagnostic radiology. It is a known fact that the risk of radiation-induced cancer is increasing, thereby necessitating the optimisation of dose in CT protocols. This study focused on determining the radiation dose of CT scans for the abdomen and lung using a 64-slice CT scanner to evaluate their correlation with body mass index (BMI). The objective of the study was to critically evaluate the relationship between BMI and radiation dose metrics in both CT lung and CT abdomen examinations. Methods: Data from 106 patients who underwent CT lung and CT abdomen examinations at an advanced diagnostic center were retrospectively analysed. The volume CT dose index (CTDIvol), dose-length product (DLP), the scan range, and cranium diameter [antero-posterior (AP) and lateral (LAT)] of the patients were documented for further analysis. Effective dose (E) and size-specific dose estimate (SSDE) were also computed. Results: The mean BMI for CT lung was recorded as 24.85 (5.65). However, the correlation between BMI and the dose metrics (SSDE, E, DLP, and CTDIvol) was not significant, with correlation coefficients of 0.1278, 0.047, 0.047, and 0.1147, respectively. In contrast, the BMI for CT abdomen scans showed a moderate correlation with E (0.5898), SSDE (0.6288), DLP (0.5898), and CTDIvol (0.612). The results demonstrate that BMI can be used as a radiation dose metric in the case of CT abdomen scans, but has no influence on CT lung scans. Conclusion: These results further suggest that BMI could provide radiation dose analysis, which in turn leads to optimisation of CT scan parameters.